Socialization of Digital Innovation Strategies to Enhance SME Sales and Community Self-Sufficiency in Kayu Manis Village - Murlena Murlena; Nurfitri Andayani; Chandra Yuliansyah; Lia Andiani; Rachmat Hidayat; Putri Milanda Bainamus; Edy Susanto; Cindy Aprilyanti; Radiyah Ramadana; Maslukin Maslukin (Asosiasi Profesi Multimedia Indonesia, 2024)
This community service focuses on empowering Micro, Small, and Medium Enterprises (MSMEs) in Kayu Manis Village, Rejang Lebong Regency, Bengkulu Province, through digital transformation to improve sales performance and promote community self-sufficiency. The study utilizes a qualitative method with a case study approach, combining direct observation, interviews with MSME owners, and socialization activities conducted during the Community Service Program (KKN). The findings reveal that adopting digital strategies, such as digital marketing, digital transaction recording, and social media platforms, has led to significant improvements in the operational efficiency and revenue of MSMEs in the village. Additionally, the use of digital tools helps minimize risks associated with financial data loss while expanding the market reach of MSMEs. These results highlight the effectiveness of digital transformation in addressing challenges faced by MSMEs, fostering their growth, and enhancing community welfare. This initiative demonstrates the critical role of technology in supporting economic development and sustainability, particularly in rural areas. The outcomes of this program serve as a valuable model for implementing similar efforts in other regions facing comparable challenges.